2022
DOI: 10.1007/s40615-022-01265-y
|View full text |Cite
|
Sign up to set email alerts
|

Place, Race, and Case: Examining Racialized Economic Segregation and COVID-19 in Louisiana

Abstract: Early COVID-19 pandemic data suggested racial/ethnic minority and low-income earning people bore the greatest burden of infection. Structural racism, the reinforcement of racial and ethnic discrimination via policy, provides a framework for understanding disparities in health outcomes like COVID-19 infection. Residential racial and economic segregation is one indicator of structural racism. Little attention has been paid to the relationship of infection to relative overall concentrations of risk (i.e., segrega… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 102 publications
1
3
0
Order By: Relevance
“…With respect to vaccination against COVID-19, 35.9% of Blacks and 62.6% of whites in Louisiana have been vaccinated (Louisiana Office of the Governor, 2020 ). A similar racial disparity has been found throughout the United States (Gaynor and Wilson, 2020 ; Scott et al, 2022 ; Centers for Disease Control & Prevention report, 2020 ; Taylor et al, 2022 ).…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…With respect to vaccination against COVID-19, 35.9% of Blacks and 62.6% of whites in Louisiana have been vaccinated (Louisiana Office of the Governor, 2020 ). A similar racial disparity has been found throughout the United States (Gaynor and Wilson, 2020 ; Scott et al, 2022 ; Centers for Disease Control & Prevention report, 2020 ; Taylor et al, 2022 ).…”
Section: Introductionsupporting
confidence: 59%
“…They also reported spatial clusters of social vulnerability, with an associated increase in mortality rate. Other studies include those of Taylor et al, ( 2022 ), who showed the disproportionate effect of COVID-19 among Blacks; Gaynor et al ( 2020 ), who used the SVI and found racial disparities in COVID-19 outcomes; and Scott et al ( 2022 ), who used geographically weighted regression models and found racial and economic segregation in COVID-19 cases. In addition, other recent studies have found a positive association between COVID-19 incidence and mortality (Madhav et al, 2020 ; Nayak et al, 2020 ; Kim et al, 2020 ; Karaye et al, 2020 ; Selden et al, 2020 ), which agreed with our findings.…”
Section: Discussionmentioning
confidence: 99%
“…The spatial interdependence between spatial units allows us to estimate the impact of explanatory variables on the outcome variable [27][28][29]. For health research, this method is broadly used to ascertain neighborhood-level determinants for various health outcomes [30][31][32]. The general specification for a spatial autoregression model is given by: where Y and X denote the vector of observations on the dependent and independent variables, respectively; W and M denote spatially weighted matrices that parameterize the location and distance between units; and refer to the spatially correlated error and residual, respectively; denotes the spatially autoregressive coefficient; and denotes the independently distributed disturbance [27,28].…”
Section: Analytic Planmentioning
confidence: 99%
“…On 1 April 2020, the Louisiana Department of Health reported over 2,500 COVID-19 cases, and by 14 April 2020, the state had over 15,000 cases, averaging 500 new cases per day, and more than 1,000 COVID-19–related deaths ( 27 , 28 ). Similar to other areas in the United States, an alarming race-based disparity in COVID-19 mortality began to emerge quickly in Louisiana ( 29 ). Early analysis estimated that over 70% of all mortalities were among Black Louisianans, despite Black residents making up just 32% of the state’s population ( 30 , 31 ).…”
Section: Coronavirus In Louisianamentioning
confidence: 99%